Trade in services and development: Policy percepction in Chile - López, Dorotea (2018)
Trade in services and its positive relation with countries’ development has been pointed out by different Chilean governments to improve services exports in order to reach diversification in its basket and add value to exports. Since the first decade of the 2000, the State has implemented a series of programs and strategies directed to achieve this objective. However, the matrix remains anchored in natural resources, particularly copper. Although trade in services has increased, it has not done so as expected. For this work several experts from the public, private and academic sector, civil society and NGOs were interviewed to collect their perception on policies that promoted services exports, implemented in the period 1990-2014. For a better understanding of the results, three overlapping levels are distinguished in a logical hierarchy from greater to lesser extent: Level I: Considerations on economic doctrines and corporate cultures. Level II: Considerations on the specificity of service industry and economic considerations. Level III: Considerations on specific policies and instruments. Some conclusions and recommendations are presented at the end.